DAMPAK RELOKASI PASAR TERHADAP KONDISI SOSIAL EKONOMI PEDAGANG DI PASAR PADANG PANJANG KOTA PADANG PANJANG SUMATERA BARAT - Imardayeti "; T. Romi Marnelly (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2020)
This research was conducted in Padang Panjang precisely at the relocation site of Padang Panjang Market in Padang Panjang, West Sumatra. The purpose of this study is to determine the impact caused by the relocation. The topic of this research focus is on the social and economic impacts after the relocation of the Padang Panjang Pusat Market. The technique of determining the sample is simple random sampling by using the Slovin formula and setting a sample of 92 respondents. The author uses descriptive quantitative methods and data instruments in this study are observation, questionnaires and documentation. The study found that this market relocation had a positive impact on the social conditions of traders where traders found a more appropriate and comfortable place to trade but this relocation also had a negative impact in terms of declining trader income due to lack of buyer interest in this new market. This lack of interest in buying is due to the multilevel market, so buyers rarely visit the upper floors of the market building and also because there are traders who sell similar goods in areas outside the market so that traders on the 2nd and 3rd floors of the market experience empty buyers. Keywords: Relocation, Impact, Social, Economy